THE STRATEGY OF USING PERSUASIVE ESSAY IN ENGLISH FOR MEDICAL ACADEMIC WRITING - Ellie Setyo Wahyuni (Institut Teknologi Sepuluh Nopember, 2014)
Writing persuasive essay has the purpose of providing some techniques in organizing the idea and constructing the sentences in coherence. The content of this essay contains the health issue and medical terms. The students of medical faculty are expected to make a good persuasive essay in order to find out the recommendation solution of a health problem through the strategies (1) brainstorming (2) mapping (3) the 5 W’s (4) setting thesis statement (5) providing fact, statistic, and example (5) conclusion. The techniques have improved the student writing as the essays have been evaluated and given positive input on the content and development of paragraphs. This academic writing aims to give some practices for the Medical Faculty students of Hang Tuah University in order to produce a good persuasive essay in term of coherence, sentence structure, and organization.